ANALISIS STRATEGI PEMASARAN DAN FAKTOR KEBERHASILAN USAHA UMKM KOPI KELILING JOERAGAN DI MEDAN - Zainarti Zainarti; Tia Aprilia; Witri Febriani Panggabean; Tri Purnama Sari; Zidan Choiril Akmal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the marketing strategy and identify factors influencing the success of the Kopi Keliling Joeragan SME in Medan. The increasingly competitive coffee beverage maintain and increase sales. The research method used is descriptive qualitative through interviews with the business worker, field observations, and supporting documentation. The results show that the marketing strategy implemented includes the implementation of the marketing mix (product, price, place, promotion), menu innovation, competitive pricing, strategic location selection, and the use of social media as a promotional tool. In addition, business success factors are influenced by product quality, service, operational management, customer loyalty, and the ability to adapt to market trends. This study provides recommendations for improving marketing effectiveness through optimizing digital marketing, expanding marketing routes, and periodically evaluating service quality. business demands that every business owner implement effective marketing strategies to